Do firm and board characteristics affect financial performance? - Ghazali, Nur Mimi Najihah; Mahmud, Radziah; Mohd Azhari, Nor Khadijah (GADING Journal for the Social Sciences, 2022)
Due to the acceleration of corporate fraud, misdemeanours, negligence, and immense loss of shareholders' investment, the concerns about the firm and board attributes have captivated people's interest, mainly due to the corporate scandals affecting various worldwide corporations. Weak corporate governance policies ultimately result in the collapse of businesses. The issue highlights the need for a better understanding of the impact of corporate governance on corporate performance. Thus, this study aims to examine how firm characteristics (leverage, liquidity) and board characteristics (board size, board independence, gender diversity, Chief Executive Officer (CEO) duality) affect a firm's financial performance in a sample of listed companies from Bursa Malaysia. The data were collected from 137 listed companies in the main market from 2017 to 2019. The results suggest that liquidity positively affects firm performance measured by Return on Asset (ROA), while leverage has a significantly negative effect on firm financial performance. Contradictory to the agency theory, the board size, board independence, gender diversity and CEO duality do not affect the firm financial performance. This study contributes to the current debate on the effect of firm and board characteristics on a firm's financial performance. The findings may also provide insight to investors and regulators.